The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1007/s10493-004-1988-2
|View full text |Cite
|
Sign up to set email alerts
|

Ticks (Acari: Ixodoidea: Argasidae, Ixodidae) of Chile

Abstract: The tick species recorded from Chile can be listed under the following headings: (1) endemic or established: Argas keiransi Estrada-Peña, Venzal and Gonzalez-Acuña, A. neghmei Kohls and Hoogstraal; Ornithodoros amblus Chamberlin; Otobius megnini (Dugès); Amblyomma parvitarsum Neumann; A. tigrinum Koch; Ixodes auritulus Neumann; I. chilensis Kohls; I. cornuae Arthur, I. sigelos Keirans, Clifford and Corwin; I. stilesi Neumann; I. uriae White; Rhipicephalus sanguineus Koch. (2) Probably established or endemic: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 48 publications
2
23
1
2
Order By: Relevance
“…The Chilean ixodids unique to the neotropical zoogeographic region and their hosts include several other endemic or established species of ixodid ticks besides I. stilesi ( I. auritulus , I. chilensis , I. cornuae , I. neuquenensis I. sigelos , I. uriae , I. taglei ) and many potential hosts (Kohls, 1969; González-Acuña and Guglielmone, 2005; Marín-Vial et al, 2007). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Chilean ixodids unique to the neotropical zoogeographic region and their hosts include several other endemic or established species of ixodid ticks besides I. stilesi ( I. auritulus , I. chilensis , I. cornuae , I. neuquenensis I. sigelos , I. uriae , I. taglei ) and many potential hosts (Kohls, 1969; González-Acuña and Guglielmone, 2005; Marín-Vial et al, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Chile has a wide range of climatic conditions and many biotopes including some similar to those in the Northern Hemisphere, as well as ixodid ticks and host animals. Ixodes stilesi is a well-characterized tick endemic to Chile (Kohls, 1956; González-Acuña and Guglielmone, 2005). It has been shown to parasitize long-tailed pygmy rice rats (colilargos) ( Oligoryzomys longicaudatus ) and pudu deer ( Pudu puda ), species indigenous to Southern Chile and Southwestern Argentina (Kohls, 1969; Guglielmone et al, 2006a; Guglielmone et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The record of Phalacrocorax verrucosus Cabanis 1875 (= Leucocarbo verrucosus) in Isla Navarino, southern Chile (Lahille, 1905), is controversial since this cormorant species is endemic to the Kerguelen Islands (South Indean Ocean) (Fonteneau and Cook, 2013). Therefore, this record is considered as an erroneous host diagnosis (González-Acuña and Guglielmone, 2005).…”
Section: Diversity Of Hosts and Geographic Distributionmentioning
confidence: 99%
“…Unlike fleas, which can be found throughout Chile, ticks have a more specific geographic distribution. A. tigrinum has been reported in Pirque and Santiago (Metropolitan District) (Abarca et al 2013), Nahuelbuta National Park (Araucanía District), Arauco, Concepción (Biobío District), Valparaíso and Santo Domingo (Valparaíso District) (González-Acuña and Guglielmone 2005); R. sanguineus can be found from Viña del Mar (Valparaíso District) (Alcaíno 1985), to Concepción (Biobío District) (Muñoz andCasanueva 2002, González-Acuña and and Aysén District (Mastropaolo et al 2008); and Amblyomma triste was first found in rural areas near the city of Arica (Abarca et al 2012).…”
Section: Introductionmentioning
confidence: 99%